No-code approaches to developing ELT resources with generative artificial intelligence. - Shin, Dongkwang; Lee, Jang Ho; Lee, Eunjin; Lee, Yongsang (ELT Journal: English Language Teaching Journal, 2026)
In this series, we explore technology-related themes and topics. The series aims to discuss and demystify what may be new areas for some readers and to consider their relevance for English language teachers. Advances in the no-code approach that uses generative artificial intelligence (GenAI) have enabled practitioners to develop ELT resources and tools without having programming expertise. More recently, within the ELT field, vibe coding has emerged. This approach allows instructors to develop and revise customized apps by interacting with GenAI and by using natural language alone. These innovations hold significant promise for ELT because teachers can now create resources such as chatbots for language practice, automated essay-scoring tools, and language exercise apps tailored to their needs, without relying on IT professionals. This feature article introduces three currently available approaches to developing a GenAI-mediated tool and discusses their merits and challenges in the ELT domain.